Introduction to marine biology - Karleskint, George (Brooks/Cole Cengage Learning, 2010)
This undergraduate textbook explores the ways in which marine organisms interact with each other and with their physical environment, and explains the importance of marine ecosystems to terrestrial ecosystems and to humankind. Hundreds of color photographs are provided. The second edition adds sections on population dynamics, marine viruses, and coral diseases.